2013
DOI: 10.1016/j.ijhydene.2013.02.145
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of confined, vented methane-hydrogen explosions using a computational fluid dynamic approach

Abstract: This is a repository copy of Prediction of confined, vented methane-hydrogen explosions using a computational fluid dynamic approach. ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 15 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Lowesmith et al [16] demonstrated the contribution of indoor equipment and pipelines to shock wave overpressure and flame propagation velocity by means of unconstrained explosion experiments with large scale gas explosions. Based on Lowesmith's experimental results, Woolley et al [17] further explored the quantitative distribution of overpressure and flame speed during methane/hydrogen explosion and unconstrained venting processes under the obstruction of multiple obstacles using computational fluid dynamics (CFD) techniques. Valeria et al [18] and Gubba et al [19] investigated the effect of characteristic parameters of single/continuous obstacles on indoor gas explosion and unconstrained venting processes using large eddy simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Lowesmith et al [16] demonstrated the contribution of indoor equipment and pipelines to shock wave overpressure and flame propagation velocity by means of unconstrained explosion experiments with large scale gas explosions. Based on Lowesmith's experimental results, Woolley et al [17] further explored the quantitative distribution of overpressure and flame speed during methane/hydrogen explosion and unconstrained venting processes under the obstruction of multiple obstacles using computational fluid dynamics (CFD) techniques. Valeria et al [18] and Gubba et al [19] investigated the effect of characteristic parameters of single/continuous obstacles on indoor gas explosion and unconstrained venting processes using large eddy simulation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al 7 , 8 studied the effects of added hydrogen on the characteristic parameters of methane-air explosion pressure and temperature through experiments and numerical simulations and found that adding hydrogen can effectively increase the explosive reaction activity and increase the explosion pressure and temperature. Woolley et al 9 established a mathematical model of the explosion pressure of gaseous hydrogen-methane-air mixtures, and the results showed that the addition of hydrogen can significantly increase the explosion pressure and temperature, thus increasing the explosion risk. Zhang et al 10 , 11 dynamically measured the explosion limits of methane-hydrogen mixtures with different components in a horizontal experimental pipeline.…”
Section: Introductionmentioning
confidence: 99%